Electronic and magnetic properties of the different phases of Ti 4O7 from density functional theory - Weissmann, Mariana Dorotea (2011)
Ab initio calculations using the local spin-density approximation plus Hubbard U (LSDA+U) method have been performed for the three reported phases of Ti4O7. Using the experimental structural parameters, we find that the electronic and magnetic properties are qualitatively different for each phase. The low-temperature structure is an antiferromagnetic semiconductor, with bipolarons arranged symmetrically in chains, separated by other nonmagnetic ion chains. The intermediate-temperature structure also contains bipolarons, but in a much more complicated order, in addition to unpaired magnetic Ti3+ ions and nonmagnetic Ti4+ ions. It has a smaller band gap than the low-temperature one. The high-temperature structure is metallic, and different distributions of Ti3+ and Ti4+ ions can be found that are almost degenerate.